Glaucoma Implant Tube Lumen Obstruction Visualized Using Anterior Segment Optical Coherence Tomography. Issue 3 (March 2018) - Nakakura, Shunsuke; Noguchi, Asuka; Noguchi, Santaro; Hirose, Yuka; Niimi, Koji; Tabuchi, Hitoshi; Kiuchi, Yoshiaki
Abstract : We report a case of glaucoma implant tube lumen obstruction visualized with anterior segment optical coherence tomography (ASOCT) and present its surgical management. The patient was a 66-year-old man with refractory glaucoma associated with traumatic aphakia in the right eye after trabeculectomy, several bleb needling procedures, and scleral fixation of the intraocular lens with pars plana vitrectomy. Finally, we performed Baerveldt implantation at the pars plana of the temporal inferior quadrant with a several Sherwood slit. However, his intraocular pressure (IOP) was >30 mm Hg despite maximum medication for several weeks. We attempted second vitrectomy and completely removed vitreous around the tube tip; however, his IOP remained around 40 mm Hg for several days after the surgery. Therefore, we suspected tube obstruction at the extraocular point of the tube lumen and used ASOCT for assessment. ASOCT revealed material in the tube lumen. We pulled out the tube and then crushed and extruded the obstructing material from the tube tip. We then refixed the tube at the same place and achieved good IOP control after the surgery. Our findings indicate that ASOCT is useful for diagnosing glaucoma implant tube lumen obstruction and surgical decision-making.